Typology of Personal Pronouns in Austronesian Languages in Indonesia - Adelawati, Munzila; Hendrokumoro, NFN (Balai Bahasa Kalimantan Tengah, 2025)
This research aims to examine typology of personal pronouns in Austronesian language families in Indonesia with a particular focus on phoneme variation and syntactic patterns. This research takes examples from five regional languages: Bengkulu Malay, Belitung Malay, Pontianak Malay, Rejang, and Lembak. Data collection involved classifying personal pronouns according to the '1/2/3' person system as proposed in Dixon’s theory of personal pronouns. These pronouns were then analyzed within sentence structures to observe their syntactic behavior and then the researcher looked for similarities that characterize the language as an Austronesian family, as well as identifying its distinctiveness. The results of this study show that the five languages studied have similarities that characterize the language as part of the Austronesian family. In addition, there are differences in phonemes that characterize each language. For example, the use of the word “aku” to refer to the first person singular pronoun known in all the languages. However, phonological variations occur, in Rejang, the word “aku” undergoes a phoneme change to “uku”. In syntactic system all the languages studied have a system of Subject, predicate, then object. The findings in this study show phonological and syntactic dynamics that enrich the diversity of the syntax that enriches the linguistic diversity in the Austronesian family in Indonesia. These dynamics are influenced by various factors, such as social, history, and geography.